#AzizAnsariToo?: Desi Masculinity in America and Performing Funny Cute. Issue 3 (3rd July 2019) - Na, Ali
Abstract: By attending to racialized tropes of masculinity and sexuality in U.S. media, this article explores how the #MeToo response to comedian Aziz Ansari is supported by a history of Asian American masculine media representation in the United States. The article forwards two theoretical concepts—Desi masculinity and performing funny cute—to explain the cultural response to Ansari as simultaneously desexualized as sexually undesirable and sexually deviant in his noncompliance with white normative masculinity. Through a critical cultural approach, these concepts thus offer a theoretical feminist approach to #MeToo that is positioned within histories of accumulated and perpetually reiterated tropes of racialized gender and sexuality.